Reduced nuclear factor-κB repressing factor: a link toward systemic inflammation in COPD - Lee, Kang-Yun; Ho, Shu-Chuan; Chan, Yao-Fei; Wang, Chun-Hua; Huang, Chien-Da; Liu, Wen-Te; Lin, Shu-Min; Lo, Yu-Lun; Chang, Ya-Ling; Kuo, Lu-Wei; Kuo, Han-Pin (The European respiratory journal, 2012)
Chronic systemic inflammation is implicated in the systemic manifestations and, probably, the excess mortality risk of chronic obstructive pulmonary disease (COPD). The role of nuclear factor (NF)-κB repressing factor (NRF), a DNA-binding, protein-inhibiting NF-κB response gene, in human diseases has not been explored. We hypothesised that the NRF-negative regulatory mechanism is impaired in COPD peripheral blood mononuclear cells (PBMCs) leading to excessive interleukin (IL)-8/CXCL8 production. NRF expression, NF-κB activation, IL-8/CXCL8 release and intracellular oxidative stress were assessed in PBMCs of normal subjects and stable COPD patients. Primary PBMCs with NRF overexpression, NRF knockdown and exposure to H 2 O 2 were used to elucidate the mechanisms. Stable COPD patients, especially those with severe COPD, showed decreased NRF expression, enhanced NF-κB activation and increased IL-8/CXCL8 release in PBMCs compared with normal subjects. This was associated with reduced NRF and increased RNA polymerase II occupancy at the IL-8/CXCL8 promoter. NRF knockdown enhanced IL-8/CXCL8 production in normal PBMCs, whilst NRF overexpression attenuated IL-8/CXCL8 production. Intracellular oxidative stress was increased in COPD PBMCs. H 2 O 2 -decreased NRF expression and -enhanced IL-8/CXCL8 production was augmented in COPD PBMCs. NRF expression is reduced in PBMCs of stable COPD patients, probably through oxidative stress, leading to increased production of IL-8/CXCL8 and potentially chronic systemic inflammation.